Job Offers as A Mode of Human Trafficking Criminal Acts From the Perspectives of Positive Law and Islamic Law - Dinda Suciana Rambe; Athaya Khalis Kafi (AT-TAFAHUM: Journal of Law, 2019)
It's important to note that Indonesia is one of the largest suppliers of migrant workers in Asia. Migrant workers are recruited through various means, including both legal (official) and illegal (smuggling) methods. The recruitment of illegal migrant workers has always been linked to slavery, which is one of the forms of human trafficking. In fact, human trafficking crimes have many forms and variations, generally carried out to extort and oppress victims for profit. Although various fundamental prevention strategies have been formulated and implemented, the social reality is that various obstacles are encountered in preventing human trafficking through the placement of migrant workers. Therefore, cooperation and synergy between all individual sectors, law enforcement agencies, and the government are needed.